2015
DOI: 10.1016/bs.ctdb.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Palatogenesis

Abstract: Palatogenesis involves the initiation, growth, morphogenesis, and fusion of the primary and secondary palatal shelves from initially separate facial prominences during embryogenesis to form the intact palate separating the oral cavity from the nostrils. The palatal shelves consist mainly of cranial neural crest-derived mesenchyme cells covered under a simple embryonic epithelium. Growth and patterning of the palatal shelves are controlled by reciprocal epithelial-mesenchymal interactions regulated by multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 114 publications
2
125
0
1
Order By: Relevance
“…*P<0.05 (two-tailed t-test). fusion of facial growth centers that are largely composed of cNCCderived mesenchyme (Jiang et al, 2006;Lan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P<0.05 (two-tailed t-test). fusion of facial growth centers that are largely composed of cNCCderived mesenchyme (Jiang et al, 2006;Lan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Morphogenesis of the upper lip and palate requires orchestrated growth and fusion of embryonic facial growth centers (Jiang et al, 2006;Lan et al, 2015). Epithelial-mesenchymal cross-talk that drives cellular proliferation and tissue outgrowth is required for closure of both the upper lip and palate.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, palatal shelves arise from the oral side of the maxillary prominences during embryogenesis and initially grow downward, flanking the developing tongue (Bush and Jiang, 2012;Lan et al, 2015). At a specific developmental stage, the palatal shelves reorient to the horizontal position above the tongue, grow towards the midline and subsequently fuse with each other to form the roof of the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent to palate development, the surrounding craniofacial structures undergo significant growth and morphogenesis. Cleft palate could result from intrinsic defects in palatal shelf growth, elevation or fusion, or from failure of the palatal shelves to contact each other at the right developmental stage due to malformation of surrounding structures (Bush and Jiang, 2012;Gritli-Linde, 2007;Hilliard et al, 2005;Lan et al, 2015). Although extensive gene knockout studies in mice in the last 25 years have shown that all major signaling pathways, including Bmp, Fgf, Notch, Shh, Tgfβ and Wnt pathways, play crucial roles in palate development, mutations in known palate development regulators have been found in <30% of cleft palate patients (Bush and Jiang, 2012;Gritli-Linde, 2007;Hilliard et al, 2005;Lan et al, 2015;Moore and Persaud, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion process is best characterised in the formation of the secondary palate where individual epithelial cells make an initial contact through extension of cell surface protrusions known as filopodia [Taya et al, 1999]. Following this initial contact, opposing epithelial surfaces make direct contact, forming a transient bi-epithelial seam which is itself removed through a combination of programmed cell death and conversion of epithelial cells into mesenchyme via epithelial to mesenchymal transformation [Xu et al, 2006;Ke et al, 2015;Lan et al, 2015]. Following successful fusion, the previously separate mesenchymal populations become united as a single continuous population.…”
mentioning
confidence: 99%